Connecting the Chains: Emotional Quotation, Ethics, and Legal Profession Ethics - Aditia Arief Firmanto; Rissa Afni Martinouva (Jurnal Hukum Novelty, 2020)
Introduction to The Problem: Emotional intelligence is in the form of feelings and emotions, and contains the direction and intensity of one’s judgment or expression of feelings expressed on the object of attitude. Emotional intelligence or Emotional Quotient (EQ) is essential. Intellectual Intelligence (IQ) cannot run properly without the participation of an emotional appreciation of the ethics of law school students. Ethics also has a massive role in determining the good and bad of human behavior, behavior, or actions. While a legal profession is a job carried out by a group of people who have the legal expertise to support their lives. Students who graduate can choose their major according to the skills taught in Higher Education. From the previous three concepts arise one main problem on how the connection between EQ-IQ, ethics, and legal profession ethics.Purpose/Objective Study: The objective of this study is to find out the correlation of emotional intelligence toward the ethics of law faculty students at Universitas Malahayati and the correlation of students’ ethics toward the legal profession.Design/Methodology/Approach: In gathering data, the researchers used quantitative (questionnaire) and qualitative methods supported by interviews. To analyze the data, the researcher used quantitative descriptive with the Linkert Scale approach, and the results of the scale are accumulated with the regress linear technique.Findings: The results of this study show that there was a significant correlation of emotional intelligence to the ethics of law school students at Universitas Malahayati. Based on the results of the hypothesis test, the value of r is 0.854 with P = 0.000 where (p <0.01). It indicates that there is a correlation between emotional intelligence and the ethics of law faculty students at Universitas Malahayati. This finding suggests that the higher the emotional intelligence, the higher the ethics, conversely the lower the emotional intelligence possessed by individuals, the lower the ethics of law school students. Additionally, the correlation of emotional intelligence toward ethics by 0.854 means that emotional intelligence has a contribution of 85.4% as a variable that affects the ethics of law school students. The remaining 14.6% of emotional intelligence is influenced by other factors. The correlation between ethics and the legal profession is that by implement ethics in the legal profession, the legal service will gain the society’s trust. People tend to lean to excellent and professional legal practitioners who have embodied the ethics in their service and their personalities.